Covid adalah pageblug: Makna dan respon masyarakat terhadap pandemi di Desa Pancasila, Sukoreno Jember - Fitriatul Hasanah; Nur Hadi; Ahmad Arif Widianto (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2021)
The last decade of 2019, the world was in an uproar with the emergence of the corona virus disease (Covid-19) outbreak which first appeared in the city of Wuhan, China and spread throughout all countries including Indonesia. Covid-19 has had a significant impact in terms of socio-cultural and economic aspects. This study aims to describe the impact of Covid-19 which has contributed to the social transformation of the people of Pancasila Village, Sukoreno in maintaining the stability of government regulations against Covid-19. This research uses qualitative methods by collecting data through interviews and observations. Interviews were conducted with the village government, religious leaders, and the people of Pancasila Village, Sukoreno. The data analysis technique used an interactive model. The results showed that the 'pagebluk' paradigm is still strongly attached to rural communities in responding to the Covid-19 virus. Pagebluk is an assumption that is believed by the community in the form of "balak" or disease. This disease is believed to provide a deterrent effect to the community because they have neglected to carry out the orders and traditions in the Pancasila Village area, Sukoreno. The existence of Pagebluk causes social and cultural transformation in the local community. Various policies, regulations and agreements related to the handling of Covid-19 are relevant to changes in the socio-religious routine in society. The impact of Covid-19 is used as a strengthening of the relationships that are built in the community in dealing with Covid-19 by using the cultural basis and local wisdom of each religion and belief. The cultural-religious basis is the main aspect of carrying out social transformation by collaborating together across religions as a form of integrity in facing Covid-19. In addition, social reality confirms that the village level FKUB (Religious Forum for Religious People) can optimize the value of mutual cooperation in order to respond to the batara times that caused riots in a religious plural society. So that religious leaders have an important role in disciplining the community to carry out religious rituals in Pancasila Village, Sukoreno. social reality confirms that the village level FKUB (Religious Forum for Religious People) can optimize the value of mutual cooperation in order to respond to the batara times that caused riots in a religiously pluralistic society. So that religious leaders have an important role in disciplining the community to carry out religious rituals in Pancasila Village, Sukoreno. Dekade terakhir tahun 2019, dunia di gemparkan dengan munculnya wabah corona virus disease (Covid-19) yang kali pertama muncul di Kota Wuhan, Cina dan menyebar ke seluruh negara termasuk Indonesia. Covid-19 menimbulkan dampak signifikan dalam aspek, sosial-budaya, dan ekonomi. Kajian ini bertujuan untuk mendeskripsikan dampak Covid-19 yang berkontribusi terhadap transformasi sosial masyarakat Desa Pancasila, Sukoreno dalam menjaga kestabilitasan peraturan pemerintahan melawan Covid-19. Penelitian ini menggunakan metode kualitatif dengan mengumpulkan data melalui wawancara dan observasi. Wawancara dilakukan dengan pemerintah desa, tokoh agama, serta masyarakat Desa Pancasila, Sukoreno. Teknik analisis data menggunakan model interaktif. Hasil penelitian menunjukkan bahwa paradigm ‘pagebluk’ masih melekat kuat terhadap masyarakat desa dalam menyikapi virus Covid-19. Pagebluk merupakan suatu asumsi yang diyakini oleh masyarakat yang berupa “balak” atau penyakit. Penyakit ini dipercaya akan memberikan suata efek jera kepada masyarakat karena telah lalai dalam menjalankan perintah dan tradisi di wilayah Desa Pancasila, Sukoreno. Adanya Pagebluk menyebabkan transformasi sosial dan budaya pada masyarakat setempat. Berbagai kebijakan, regulasi dan kesepakatan terkait penanganan Covid-19 berelevansi terhadap perubahan rutinitas sosial keagamaan di masyarakat. Dampak Covid-19 dijadikan sebagai penguat relasi yang terbangun di masyarakat dalam merentas Covid-19 dengan menggunakan basis budaya dan kearifan lokal pada masing-masing agama dan aliran kepercayaan. Basis budaya-agama menjadi aspek utama melakukan transformasi sosial dengan melakukan kolaborasi bersama lintas agama sebagai wujud integritas menghadapi Covid-19. Selain itu, realitas sosial menegaskan bahwa FKUB (Forum Keagamaan Umat Beragama) tingat desa dapat mengoptimalkan nilai kegotongroyonga guna menyikapi batara kala yang menyebabkan kerusuhan di tengah masyarakat plural beragama. Sehingga tokoh agama memiliki peran penting dalam mendisiplinkan masyarakat untu melaksanakan ritual keagamaan di Desa Pancasila, Sukoreno.